PENENTUAN KRITERIA DAN PEMASOK PADA CV. CUPU ARTAMA JAYA KABUPATEN JOMBANG - David Lutfi Hadian (Manajemen Bisnis, 2017)
This study aims to determine the supplier of frozen chicken at CV. Cupu Artama Jaya, Jombang Regency. The purpose of this research is to determine the supplier at CV. Cupu Artama Jaya, Jombang Regency.  According to the result of criteria selection, there are seven criteria used by the company, which are quality, price, delivery time, communication system, packing capability, warranty and complaint service, and management and organization. All of these categories range from very important, important, and sufficient. There are three suppliers selected according to the seven criteria, PT. Wonokoyo, UD. Puri Pangan, and UD. Phalosari. The findings show that UD. Phalosari has the greatest value of 76.89, PT. Wonokoyo gets 72.96, and the last UD. Puri Pangan gets 69.98. referring to this, UD. Phalosari is highly recommended to be the main supplier for the company.